Jurnal Potensi Jalur Tol Laut Dalam Mendukung Pengembangan Pariwisata Maritim Di Banyuwangi - Junita Garianti Tandi; Agussalim Burhanuddin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
Maritime tourism is an important sector in driving the economy of coastal areas such as Banyuwangi. With its diverse natural riches, Banyuwangi has great potential to develop tourism that focuses on the sea. However, existing accessibility constraints have become an obstacle in maximizing the potential of maritime tourism. This research aims to examine the potential of maritime toll routes in supporting the development of maritime tourism in Banyuwangi. The research methods used are literature study, secondary data analysis, as well as reviewing journals and literature studies related to this research. The research results show that the sea toll road has great potential to increase accessibility to maritime tourism destinations in Banyuwangi. With the existence of a sea toll road, travel time and transportation costs can be reduced, so that it will attract more tourists to visit destinations such as Pulau Merah Beach, Menjangan Island and Baluran National Park. Apart from that, sea toll routes can also support the development of tourism infrastructure, such as more modern tourist ports and other supporting facilities. However, this research also identifies several challenges that need to be overcome, such as maintaining maritime highways, coordination between stakeholders, and sustainable environmental management. Therefore, collaboration between the government, tourism entrepreneurs and local communities is the key to maximally exploiting the potential of this sea toll route.